2021
DOI: 10.7554/elife.65484
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic aggregation of mitochondrial proteins disrupts cellular homeostasis by stimulating the aggregation of other proteins

Abstract: Mitochondria are organelles with their own genomes, but they rely on the import of nuclear-encoded proteins that are translated by cytosolic ribosomes. Therefore, it is important to understand whether failures in the mitochondrial uptake of these nuclear-encoded proteins can cause proteotoxic stress and identify response mechanisms that may counteract it. Here, we report that upon impairments in mitochondrial protein import, high-risk precursor and immature forms of mitochondrial proteins form aberrant deposit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 56 publications
(46 reference statements)
3
72
0
Order By: Relevance
“…These findings obtained for human cells are supported by similar data for S. cerevisiae and C. elegans . In the latter case, cytosolic aggregation of mitochondrial preproteins was observed, which are known to be downregulated in AD, and the aggregation of ASYN and Aβ was enhanced because of mitochondrial protein import dysfunction [ 113 ].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…These findings obtained for human cells are supported by similar data for S. cerevisiae and C. elegans . In the latter case, cytosolic aggregation of mitochondrial preproteins was observed, which are known to be downregulated in AD, and the aggregation of ASYN and Aβ was enhanced because of mitochondrial protein import dysfunction [ 113 ].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…In certain conditions, protective mechanisms that adjust the influx of mitochondrial precursor proteins and modulate degradation systems are insufficient. If these mechanisms fail, unimported mitochondrial precursors may form aggregate-like deposits [ 136 , 177 ] ( Figure 4 ). Collecting excess precursors within insoluble deposits might reduce their toxicity and allow for safer storage [ 136 , 178 ].…”
Section: Mitochondrial Precursor Proteins Are Prone To Aggregationmentioning
confidence: 99%
“…The potential to form cytosolic deposits of mitochondrial precursors is significant in cells susceptible to protein aggregation, such as neurons. Significantly, mitochondrial precursor aggregates were shown to increase misfolding of α-synuclein or amyloid β proteins [ 177 ], oligomerization and aggregation of which are responsible for Parkinson’s and Alzheimer’s diseases.…”
Section: Mitochondrial Precursor Proteins Are Prone To Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that Tom70 not only controls the import of mitochondrial proteins, but also regulates their biogenesis. The nascent mitochondrial proteins synthesized in the cytosol are aggregation-prone and can cause cytosolic proteostasis stress and protein aggregation if not imported in a timely manner (Nowicka et al, 2021;Wang and Chen, 2015;Wrobel et al, 2015). It has been shown that impaired mitochondrial import triggers cellular responses to reduce the biogenesis of mitochondrial proteins in order to achieve a new balance between biogenesis and import of nascent mitochondrial proteins, alleviating their cytosolic accumulation and aggregation (Samluk et al, 2018;Topf et al, 2019;Wrobel et al, 2015).…”
Section: The Tom70-dependent Regulation Of Mitochondrial Biogenesis Is Involved In the Cellular Response To The Mitochondrial Import Defementioning
confidence: 99%